How is the implementation of green accounting in public hospital? - Muhammad Hasyim Ashari; Yudhi Anggoro (Journal of Islamic Accounting and Finance Research, 2021)
Purpose - The purpose of this study is to find out the implementation of green accounting in Public Hospitals in Malang and to determine the preferences of Public Hospitals in running their business.Method - This research is a descriptive quantitative study conducted by survey method. The total of population are 40 Public Hospitals in Malang Raya and the sample obtained as respondents are 37 Public Hospitals spread across Malang District, Malang City and Batu City.  The sample selection used probability sampling by sending a questionnaire to the entire population.  Result - The results showed that the green accounting practices in Public Hospitals in Malang Raya based on financial activities, social activities and environmental activities had been implemented properly and consistently. Public Hospitals with higher types tended to be better and more consistent in applying green accounting than Public Hospitals with lower types (classes).Implication - With the awareness of Public Hospitals in Malang Raya to implement green accounting in the accountability of their business activities, it can have an impact, especially on environmental sustainability and the welfare of the community around the Public Hospital from the impact of the resulting waste.Originality - The concept of green accounting can also be implemented to Public Hospitals as a public entity. On this basis, of course, it is necessary to conduct research on the implementation of green accounting in Public Hospitals as a public entity so that in its operational activities it does not only consider the financial aspects to generate profits, but also considers environmental and social aspects. As a result, its business can have an impact especially on environmental sustainability and the welfare of the community around Public Hospitals from the impact of the waste produced.